Benefits of Older Volunteering on Wellbeing: An International Comparison - Gil-Lacruz, Marta; Saz-Gil, María I.; Gil-Lacruz, Ana I. (Frontiers in Psychology, 2019)
Healthier aging implies lower health service expenditure and the possibility for individuals to make a longer and more valuable contribution to society. Lifestyles, including volunteering, affect our health. The policy implications of the present study are that it aims to broaden the state of knowledge and be useful to public decision-makers: if voluntary activities enhance the integration of older people into society, their participation will help to generate economic resources and improve their own welfare; if, however, health and participation do not show positive synergies, then policymakers must act independently in each of these fields. In this work, we focus on the societies of Chile, Mexico, and Spain because they have significantly aging populations and share common traits but also exhibit important differences. The empirical study employs micro-data from the World Value Survey (1994–1998, 2005–2009, and 2010–2014) and macro-data from the statistics of the OECD (Organization for Economic Co-operation and Development). Micro- and macro-data are merged by national and temporal identifiers. Our main results provide empirical evidence that volunteering might improve every indicator of wellbeing except happiness. Different kinds of activities have different impacts on individual wellbeing. For example, volunteering in activities related to social awareness is positive for male life satisfaction, whereas volunteering in activities related to religious issues is positive for male life satisfaction but also female happiness. In general, voluntary activities have a stronger impact on male wellbeing than female wellbeing.